TINGKAT LITERASI MEDIA BERBASIS KOMPETENSI INDIVIDU DI KALANGAN SISWA SMA NEGERI 17 MAKASSAR - Rahmawati Latief (Fakultas Dakwah dan Komunikasi, 2019)
Nowadays the mass media is experiencing very rapid development. Various positive and negative impacts certainly cannot be ignored. This impact hits parents, adults, teenagers and children. Adolescents are a group that is vulnerable to the negative effects of mass media by which media literacy movements emerge as solutive actions over concerns about negative media influences. The ability of media literacy is very necessary so that the media can be used intelligently and wisely. The purpose of this study are: (1) To determine the level of technical skills (technical expertise) of SMA Negeri 17 Makassar students in accessing computer and internet media; (2) To describe the level of critical understanding (critical understanding) of SMA Negeri 17 Makassar students in analyzing and evaluating computer and internet media content; (3) To understand the level of communicative abilities (communication skills) of SMA Negeri 17 Makassar students in establishing social relations through internet media and creating creative internet media content; (4) To find out the level of media literacy of SMA 17 Makassar students. The results of this study indicate that cumulatively the level of technical skill ability is at 99.5%, the level of critical understanding capability is at 74.7%, the level of communicative abilities is at a value of 110.3%. By referring to the values above, the level of media literacy of Makassar 17 Public High School students is 94.83% or at the Medium level.